Mapping Seyfert and LINER excitation modes in the inner kpc of NGC 3393 - Maksym, W. Peter (2016)
We mapped the extended narrowline region (ENLR) of NGC 3393 on scales of r  4 (~1 kpc) from the nucleus using emission line images of Hα λ6563, [O III]l5007, and [S II]ll6717, 6731, taken with the Hubble Space Telescope as part of the CHandra survey of Extended Emission line Regions in nearby Seyfert galaxies (CHEERS). By mapping these lines onto a spatially resolved Baldwin–Phillips–Terlevich diagram, we investigate the impact of feedback from a Compton-thick active galactic nucleus on its circumnuclear ISM. We find that the expected Seyfert-like emission within the ionization bicone (3; 770 pc). We also find a new, figure-8-shaped low ionization emission line region (LINER) cocoon enveloping the bicone and defining a sharp (100 pc) transition between higher and lower-ionization zones. These data illustrate the morphological dependence of ionization states of the ENLR relative to bicone and host gas geometries.